Walleye Sander vitreus (Mitchill) are relatively resistant to experimental infection with VHSV IVb and extant walleye strains vary in susceptibility. Issue 10 (15th September 2014) - Grice, J; Reid, A; Peterson, A; Blackburn, K; Tubbs, L; Lord, S; Huber, P; Horricks, R; Dixon, B; Bols, N C; Lumsden, J S
Abstract Compared to fathead minnow, walleye demonstrate low susceptibility to experimental infection with VHSV IVb, regardless of route of exposure or water temperature at time of infection. In triplicate and duplicate groups, walleye were intraperitoneally (i.p.) injected (102–108 pfu/fish) or waterborne‐exposed (w; 1.4 × 107 pfu mL−1) with VHSV IVb. High cumulative mortality (64–100%) and severe gross lesions associated with VHSV IVb infection were evident only in fish i.p. injected with 108 pfu at 12 °C. These fish had multifocal necrosis of several tissues including the gill and heart. There was no difference in mortality between walleye infected (w or i.p.) at 12 °C (spring stocking) compared with a declining temperature profile from 18 to 12 °C (fall stocking). There were significant differences (P < 0.05) in mortality between four extant walleye strains following i.p. infection, indicating that the choice of walleye strain for stocking might be an important consideration. Viral antigen was found in both i.p. and w‐exposed walleye using immunohistochemistry, mostly within the gill and skin of w‐exposed fish and most prominently in dermal fibrocytes. VHSV IVb was detected in multiple tissues from 6 to 21 days post‐infection using reverse transcriptase quantitative polymerase chain reaction (RT‐qPCR).